2017
DOI: 10.1088/1361-6641/aa6c02
|View full text |Cite
|
Sign up to set email alerts
|

Total ionizing dose effects in multiple-gate field-effect transistor

Abstract: This paper focuses on total ionizing dose (TID) effects induced in multiple-gate field-effect transistors. The impact of device architecture, geometry and scaling on the TID response of multiple-gate transistors is reviewed in both bulk and silicon-on-insulator (SOI) complementary metal-oxide-semiconductor (CMOS) technologies. These innovating devices exhibit specific ionizing dose responses which strongly depend on their three-dimensional nature. Their TID responses may look like the one usually observed in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…As a result, traps are formed at the silicon-oxide interface, due to the release of radiolytic hydrogen and the formation of dangling bonds [4]. The interface traps mainly manifest as negatively charged traps in n-type devices, while the opposite is true for p-type devices [25][26][27]. Figure 3 depicts the method used to assess TID effects in this work; a similar method has successfully been applied to LDMOS devices [4].…”
Section: Device Structure and Simulation Methodsmentioning
confidence: 99%
“…As a result, traps are formed at the silicon-oxide interface, due to the release of radiolytic hydrogen and the formation of dangling bonds [4]. The interface traps mainly manifest as negatively charged traps in n-type devices, while the opposite is true for p-type devices [25][26][27]. Figure 3 depicts the method used to assess TID effects in this work; a similar method has successfully been applied to LDMOS devices [4].…”
Section: Device Structure and Simulation Methodsmentioning
confidence: 99%
“…Thorough reviews are provided in [42] and [43]. Here, we stress on the role that the distribution of trapped charge in the field oxide plays for the emergence of this complexity.…”
Section: Finfets and Other Multigate Architecturesmentioning
confidence: 99%
“…In SOI FinFETs, the electrostatic potential of the gate reduces when the gate length decreases, and therefore charges trapped in the BOX dominate the TID response. Therefore, for gate lengths less than 40 nm, it is advised to use an SOI structure that gives more control over the channel, such as the gate-allaround (GAA) described in Section V [43].…”
Section: Finfets and Other Multigate Architecturesmentioning
confidence: 99%
“…Although the LTPS TFTs show great electrical properties without radiation state, noticeable decay and electrical instability are observed when the devices are irradiated by xrays. In the aspect of characteristics, some research reported the threshold voltage (V th ) shift and mobility change after xray irradiation [8][9][10]. While in the aspect of response time, many related research is studied.…”
Section: Introductionmentioning
confidence: 99%